The solution to the polynomial equation, x² + 5x + 6 = 0, is calculated as: x = -2, x = -3.
To solve a polynomial equation means to find the values of x that would make the equation true if we plugged in their values back into the equation.
Given the polynomial equation, x² + 5x + 6 = 0, to solve for the value of x, we need to factorize the equation as shown below:
x² + 3x + 2x + 6 = 0
(x² + 3x) + (2x + 6) = 0
x(x + 3) +2(x + 3) = 0
The factors of the equation would be:
(x + 2)(x + 3) = 0
x + 2 = 0
x = -2
or
x + 3 = 0
x = -3
Therefore, the solution is: x = -2, x = -3.
Learn more about solving polynomial equations on:
https://brainly.com/question/14837418
#SPJ1